Tolerance Response of the Darussalam Islamic Boarding School, Blokagung, to the Ogoh-Ogoh Celebration in Blokagung, Karangndoro, Tegalsari, Banyuwangi - Islamiyah, Hidayatul; Chotib, Moch; Abbas, Raffid (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The Ogoh-Ogoh parade is a celebration that is inherent in the Hindu community in Banyuwangi. The existence of this parade is certainly a spirit and enthusiasm for the glory of the Hindu community. For the Islamic community, including Islamic boarding schools, it is a hard slap to the concept of religious tolerance which must be implemented and accustomed to. At first glance, the Ogoh-Ogoh parade is not interesting and is not suitable to be shown and shown, especially to children. The scary form of Ogoh-Ogoh symbolizes the devil and also, the form of Ogoh-Ogoh contains pornographic elements. However, even so, Hindus have their view of Ogoh-Ogoh as a symbol of human awareness of the power of the universe and the all-powerful time. This depiction in Hindu Dharma includes the personality of Bhuta Kala. Hindus think that the Ogoh-Ogoh parade will still be celebrated and preserved. Included in one of the cultures and complements the religious rites of Hindus. It is hoped that this article will add to the body of knowledge regarding the response of the Darussalam Islamic boarding school to the Ogoh-Ogoh celebration, precisely in Karangdoro Blokagung village.